Signal Quality Assessment in Physiological Monitoring State of the Art and Practical Considerations - Orphanidou, Christina (SpringerBriefs in Bioengineering,, 2018)
This book provides a comprehensive overview of the state of the art in signal quality assessment techniques for physiological signals, and chiefly focuses on ECG (electrocardiography) and PPG (photoplethysmography) signals obtained from wearable sensors in ambulatory clinical settings. It presents the techniques currently proposed by leading researchers, as well as examples using data from clinical trials on wearable sensors for inpatient and outpatient settings. In addition, the book assesses current approaches through a practical lens by discussing the implications of deploying the various proposed systems for clinical practices and health outcomes. As such, it will be of considerable interest to both graduate students and researchers working to develop personalized healthcare applications, as well as physiological sensor software and hardware developers.